DUSP5 is methylated in CIMP-high colorectal cancer but is not a major regulator of intestinal cell proliferation and tumorigenesis - Lars Tögel (Nature Portfolio, 2018)
Abstract The ERK signalling pathway regulates key cell fate decisions in the intestinal epithelium and is frequently dysregulated in colorectal cancers (CRCs). Variations in the dynamics of ERK activation can induce different biological outcomes and are regulated by multiple mechanisms, including activation of negative feedback loops involving transcriptional induction of dual-specificity phosphatases (DUSPs). We have found that the nuclear ERK-selective phosphatase DUSP5 is downregulated in colorectal tumours and cell lines, as previously observed in gastric and prostate cancer. The DUSP5 promoter is methylated in a subset of CRC cell lines and primary tumours, particularly those with a CpG island methylator phenotype (CIMP). However, this epigenetic change alone could not account for reduced DUSP5 expression in CRC cells. Functionally, DUSP5 depletion failed to alter ERK signalling or proliferation in CRC cell lines, and its transgenic overexpression in the mouse intestine had minimal impact on normal intestinal homeostasis or tumour development. Our results suggest that DUSP5 plays a limited role in regulating ERK signalling associated with the growth of colorectal tumours, but that methylation the DUSP5 gene promoter can serve as an additional means of identifying CIMP-high colorectal cancers.